Perbandingan antara Kekuasaan Tuhan dalam Aliran Jabariyah dan Kekuasaan Manusia dalam Aliran Qadariyah - Raihan Ridho Abdillah (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the comparison between divine power in the Jabariyah school and human power in the Qadariyah school. This research uses a qualitative approach or literature study method by looking for references related to the issues of Jabariyah and Qadariyah. The formal object of this research is comparison, while the material object is the power of God in the Jabariyah school and human power in the Qadariyah school. The results and discussion in this study are, Jabariyah and Qadriyah in their concept of destiny both use the argument naqli so that they consider this to be the truth which then the proposition naqli tries to balance with reason, but from the two concepts of destiny given by the two streams each has its own loopholes. This study concludes that there is no truer concept of destiny, so further studies are needed by Muslim scholars and theologians to mediate this.